Ethnobotanical and Phytochemical Study of Bayur (Pterospermum javanicum Jungh.) on Sasak Tribe around Mount Rinjani National Park, West Lombok as a Conservation Effort - Putri Sri Andila; Tri Warseno; I Putu Agus Hendra Wibawa; I Gede Tirta (Universitas Gadjah Mada, 2021)
Pterospermum javanicum Jungh. (Bayur) is a species belongs to the Pterospermum genera (Malvaceae). Several species of Pterospermum had been reported for their ethnobotanical usage, but the studies about ethnobotany information of Bayur and its secondary metabolite compounds were still limited which have been published. This study aimed to observe the ethnobotanical usage of Bayur and to examine the phytochemical contents of the acetone extract of Bayur flower from West Lombok. The ethnobotany information of Bayur was obtained through interviews with local people and more information on the ethnobotanical records of P. javanicum (Bayur) was conducted by reviewing the scientific literature. The chemical compounds of Bayur flower were analysed by the GC-MS method. The results revealed that Bayur was used by the Sasak community around Gunung Rinjani National Park West Lombok for various purposes, such as traditional medicines, beverages, rigging, and building material. The phytochemical analysis showed that the acetone extract of Bayur flower from West Lombok contained 38 identified chemical components, representing 93.78% of the total compounds. The major contents of them were Lupeyl acetate (10.68%), p-n-Amylphenol (8.16%), Lauric acid (7.31%), N-(Methyl-d2)- Aniline (5,82%), and Pentanal (5.07%). This report was the first publication about the phytochemical contents of Bayur flower. It is expected that this study gives further information on the potentials of Bayur, especially about its secondary metabolite to support and prove the truth of the cultural concept of society in utilizing Bayur as a medicinal plant.